A genomic approach reinforces a hypothesis of mitochondrial capture in eastern Australian rosellas. (7th December 2016) - Shipham, Ashlee; Schmidt, Daniel J.; Joseph, Leo; Hughes, Jane M.
Abstract: Recently, there have been contradictory results regarding relationships among 3 Australian parrot species known commonly as the Northern ( Platycercus venustus ), Pale-headed ( P. adscitus ), and Eastern rosella ( P. eximius ). An early phylogenetic analysis of the rosella genus Platycercus found that P. adscitus and P. eximius, 2 species putatively forming a hybrid zone, were sister taxa, while the geographically isolated P. venustus was in turn their sister taxon. However, a recent reexamination using multilocus sequence data found that evolutionary relationships differed depending on marker choice. Mitochondrial DNA (mtDNA) supported the earlier finding, but nuclear sequence data reflected an alternative relationship aligning P. adscitus and P. venustus as sister taxa. Two hypotheses were proposed to reconcile the discordance: (1) incomplete lineage sorting, and (2) mtDNA introgression from P. adscitus into populations of P. eximius . To clarify the relationships among these 3 species and to distinguish between the proposed hypotheses, restriction site-associated DNA (RAD) sequencing data from 23 individuals (∼4 individuals per subspecies) were examined. Species trees were generated based on datasets either excluding loci with missing data (393 loci) or including them (5 nonoverlapping subsets of 1, 000 loci). Findings strongly supported a sister relationship between P. adscitus and P. venustus (posterior probabilities of 1 at all nodes), suggesting that the discordant patterns previously identified may have been the result of mitochondrial introgression and/or capture. This and other potential explanations are discussed.